Alter und Gesundheit: Eine Bestandsaufnahme aus Sicht der Gesundheitsberichterstattung. - Saß, Anke-Christine; Wurm, Susanne; Scheidt-Nave, Christa (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2010)
With advancing age, there is a significant increase in the number of health problems; at the same time, the complexity of the existing impairments increases. In addition to the diagnosed somatic and psychological illnesses, functional disorders and disabilities as well as the self-assessed health of the individual play an important role. Health in old age is an important individual and societal topic today and in the future. In order to plan health politics, mapping of morbidity and prognosis are important. They require representative, valid, current, and comparable data over time. Databases of the health reporting in the area of senior citizens have improved in recent years. However, data are still missing, for example, in the area of not being able to fully take part in daily life. Research is needed, because of the specificity of health problems in the elderly, including the survey methodology and the selection of suitable indicators. © Springer-Verlag 2010.
Keywords: Data; Health; Health reporting; Morbidity; Old age